Manutenção preditiva: análise e propostas de intervenção em redutores de velocidade após teste de fluido lubrificante - Nunes Filho, Marcos Rogério Vieira (2022)
All equipment or mechanical system is doomed to deterioration processes, causing the appearance of failures that can compromise the continuity and quality of an entire production process. In an attempt to predict such defects, predictive maintenance techniques are used. Among these, one that stands out when it comes to gearbox maintenance is the analysis of lubricating oil. Such a technique is capable of identifying the first signs of wear on a component. The identification is made by studying the quantification of particles, viscosity analysis, magnetic particle index, total acidity number and the like. Oil analysis is performed using laboratory techniques that involve different equipment and methods for each test performed. In this work, the analysis of lubricating oil was used to evaluate the conditions of six speed reducers of a house paint industry, where parameters such as wear index and lubricant viscosity analysis were evaluated, for example. To this end, a bibliographic study was carried out on the types of maintenance, on the tests carried out on the oil samples and on the types of lubricant. Through the results obtained through the tests carried out, a classification was made regarding the status that each sample fits and intervention actions were proposed for each of the evaluated gearboxes that would lead to solving the problem elucidated through the oil analysis.